Unique In-school Garden and Nutrition Intervention Improves Vegetable Preference and Food Literacy in Two Independently Conducted Evaluations (P16-040-19). (13th June 2019) - Mitchell, Megan; Goldsworthy, Natalie; Roth, Ashley; Gonzalez-Avram, Cristina
Abstract: Objectives: In 2016, Big Green (BG), a youth wellness and school garden organization, and Common Threads (CT), a health and wellness nutrition education organization, co-created Garden Bites (GB), a garden-based nutrition and health curriculum for PreK-8th students. GB is a fifteen lesson, school-based program featuring nutrition education, hands-on snack preparation, and outdoor garden activities. In 2018, CT evaluated GB independently from BG who supplemented the program with additional gardening activities (EGI). The purpose of the evaluation was to assess Big Green and Common Threads' shared organizational impact areas: increasing knowledge and preference for fruits and vegetables and food literacy (nutritional skills and knowledge). Methods: For GB only intervention, 81 students were evaluated pre-post intervention using survey methodology. For the GB plus EGI, a total of 820 students across four urban school districts took pre- and post-treatment surveys during the course of one semester. Results: GB alone was found to significantly improve (all P  < .05) vegetable preference, vegetable exposure, and fruit and vegetable consumption. When GB was complemented with EGI, it was found to significantly improve (all P  < .05) vegetable likability and preferences, healthy eating expectations, and perceived access to healthy food and parental support at home. Conclusions: GB was found to show promising, repeated results as a school-based intervention to improve student nutrition knowledge and food literacy, which are both important precursors to improved health behaviors. Results from this evaluation will be used to improve Garden Bites and EGI as well as inform school garden programming more widely. Funding Sources: Both organizations are 501(c)(3) non-profits funded by grants.